The recent advances of mast cells in the pathogenesis of atopic dermatitis - Xiao, Zhenzhen; Zhuo, Yunqian; Li, Rui; Tan, Yingjian (Frontiers in Allergy, 2025)
Mast cells play a critical role in the pathogenesis of atopic dermatitis (AD), a chronic inflammatory skin disease characterized by itch, eczema, and barrier dysfunction. These immune cells are abundant in the skin and are activated in response to allergens, irritants, and microbial products. Upon activation, mast cells release a variety of mediators, including histamine, proteases, cytokines, and chemokines, which contribute to the inflammation and pruritus observed in AD. Recent studies have highlighted the importance of mast cell-derived IL-4, IL-13, and IL-31 in promoting Th2-type immune responses and itch sensation. Moreover, interactions between mast cells and sensory neurons may further exacerbate neuroimmune inflammation. Mast cells also influence skin barrier integrity by modulating keratinocyte function and disrupting tight junctions. Their numbers and activation state are often elevated in AD lesions, correlating with disease severity. Targeting mast cell activation or blocking their mediators has shown promise in preclinical models, offering potential therapeutic strategies. Overall, mast cells are increasingly recognized as key contributors to the initiation and amplification of AD, making them an important focus for understanding disease mechanisms and developing new treatments.